Analisis Studi Kelayakan Bisnis Usaha Dessert Modern Melalui Pendekatan SWOT: Studi Kasus Makna Dessert di Kota Bandung - Dwi Yulistiani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The development of the culinary industry in Indonesia, particularly in the dessert sector, has experienced significant growth along with changes in people's lifestyles and the use of social media as a promotional tool. This study aims to analyze the business feasibility of Makna Dessert as a modern dessert business in Bandung City using a business feasibility study approach and SWOT analysis. The research method used was quantitative descriptive, with data collected through a survey of 36 respondents. Data were analyzed based on consumer behavior, marketing, and financial aspects, and formulated into a SWOT analysis to determine the business's strategic position. The results indicate that Makna Dessert's strengths lie in product quality, visual appearance, and price appropriateness, as well as significant market opportunities. Overall, Makna Dessert is deemed feasible to operate and expand with the right management strategy.